2015
DOI: 10.1039/c5nr03853g
|View full text |Cite
|
Sign up to set email alerts
|

CO2 controlled flocculation of microalgae using pH responsive cellulose nanocrystals

Abstract: Cellulose nanocrystals were grafted with imidazole functionalities up to DS 0.06 using a one-pot functionalization strategy. The resulting nanocrystals were shown to have a pH responsive surface charge which was found to be positive below pH 6 and negative above pH 7. These imidazolyl cellulose nanocrystals were tested for flocculation of Chlorella vulgaris using CO2 to induce flocculation. Up to 90% flocculation efficiency was achieved with 200 mg L(-1) dose. Furthermore, the modified cellulose nanocrystals s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 37 publications
1
46
1
Order By: Relevance
“…Separation of microalgae from the growth medium is an important process for harvesting this valuable biomass for use in biofuel production. Biodegradable polymers such as cellulose nanocrystals (CNC) are attractive options for this purpose . Swinging the pH to trigger the flocculant, however, leads to the accumulated salts eventually damaging the microalgae growth medium.…”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Separation of microalgae from the growth medium is an important process for harvesting this valuable biomass for use in biofuel production. Biodegradable polymers such as cellulose nanocrystals (CNC) are attractive options for this purpose . Swinging the pH to trigger the flocculant, however, leads to the accumulated salts eventually damaging the microalgae growth medium.…”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
“…modified CNC with imidazole to obtain a pH‐responsive flocculant possessing a pKa close to that of H 2 CO 3 in water, so that they could use CO 2 as a trigger for the flocculant, instead of an acid or a base. They observed that the flocculation efficiency of modified CNC decreased from 90% at pH 4 to 20% at pH 8, an indication of the polymer becoming CO 2 switchable . Other examples of CO 2 ‐responsive flocculants are listed in Table 4 .…”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
“…Because of these properties, these materials have many potential applications in electronics, food and tissue engineering. In the microalgae field, cation-modified cellulose nanocrystal (CNC) has recently been applied to induce flocculation for dewatering during biofuel production5. The results revealed that the cation-modified CNC flocculated microalgae via ion neutralization, but anion-modified CNC did not.…”
mentioning
confidence: 99%
“…[7][8][9] Beside this initial application, the potential of CNCs to be used as a building block in more complex systems has been recognised and they have since been investigated for applications ranging from optical materials, [10,11] to permselective membranes, [12] electrode modifiers for electrochemical sensors, [13] supercapacitors, [14][15][16] and algae flocculants with and without pH responsiveness. [17,18] While many of these applications can make use of "unmodified" cellulose nanocrystals, i.e. as extracted from native cellulose, further expansion of the applications of these excellent materials in advanced materials requires the introduction of additional functionalities through surface modification.…”
Section: Introductionmentioning
confidence: 99%